(untitled) (Indonesian Health Justice Review, 2025)
Food security and nutrition are fundamental components of health justice, yet Indonesia faces persistent challenges in addressing malnutrition and improving public health outcomes. This paper examines the role of Indonesia’s food policies in promoting health justice, focusing on the link between food security, nutrition, and health disparities. Through policy analysis and field research, the study explores the effectiveness of current food security programs in addressing issues such as undernutrition, micronutrient deficiencies, and obesity. The research identifies systemic barriers to achieving food justice, including unequal access to healthy foods in rural and urban areas, the prevalence of highly processed foods, and the lack of nutrition education in schools and communities. The paper argues that Indonesia’s food policies must be restructured to prioritize equitable access to nutritious food, particularly for vulnerable populations such as children, the elderly, and low-income families. Recommendations include increasing support for local food systems, promoting sustainable agriculture, and expanding public health campaigns on nutrition and healthy eating habits. The paper concludes that achieving food security and nutrition justice is essential for improving public health and reducing health disparities in Indonesia.